Understanding of metal-insulator transition in VO2 based on experimental and theoretical investigations of magnetic features. Issue 1 (December 2018) - Zhang, R.; Fu, Q.; Yin, C.; Li, C.; Chen, X.; Qian, G.; Lu, C.; Yuan, S.; Zhao, X.; Tao, H.
Abstract The metal-insulator transition temperatureT c in VO2 is experimentally shown to be almost the same as a magnetic transition temperatureT m characterized by an abrupt decrease in susceptibility, suggesting the evidence of the same underlying origin for both transitions. The measurement of susceptibility shows that it weakly increases on cooling for temperature range ofT > T m, sharply decreases nearT m and then unusually increases on further cooling. A theoretical approach for such unusual observations in susceptibility nearT m or below is performed by modeling electrons from each two adjacent V4+ ions distributed along V-chains as a two-electron system, which indicates that the spin exchange between electrons could cause a level splitting into a singlet (S = 0) level of lower energy and a triplet (S = 1) level of higher energy. The observed abrupt decrease in susceptibility nearT m is explained to be due to that the sample enters the singlet state in which two electrons from adjacent V4+ ions are paired into dimers in spin antiparallel. By considering paramagnetic contribution of unpaired electrons created by the thermal activation from singlet to triplet levels, an expression for susceptibility is proposed to quantitatively explain the unusual temperature-dependent susceptibility observed at low temperatures. Based on the approach to magnetic features, the observed metal-insulator transition is explained to be due to a transition from high-temperature Pauli paramagnetic metallic state of V4+ ions to low-temperature dimerized state of strong electronic localization.